Polymer Solar Cells: Fabricating High Performance, Donor–Acceptor Copolymer Solar Cells by Spray‐Coating in Air (Adv. Energy Mater. 4/2013). Issue 4 (10th April 2013) - Wang, Tao; Scarratt, Nicholas W.; Yi, Hunan; Dunbar, Alan D. F.; Pearson, Andrew J.; Watters, Darren C.; Glen, Tom S.; Brook, Andrew C.; Kingsley, James; Buckley, Alastair R.; Skoda, Maximilian W. A.; Donald, Athene M.; et al.
<x xml:space="preserve">Abstract</x> David G. Lidzey, Tao Wang, and co‐workers fabricate on page 505 high performance donor–acceptor carbazole based copolymer solar cells using spray coating in air. A range of inks have been designed to deliver uniform films over large area. The effects of solvent, substrate temperature and active layer thickness on device efficiency are explored. Vertical stratification of PCBM in the blends is revealed by neutron scattering. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>